CHEMICAL CONSTITUENTS OF GEUM RIVALE L. AND THEIR BIOLOGICAL ACTIVITY - Anastasia A. Orlova; Maria N. Povydysh (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2020)
The aim of the study is to review the literature data on the chemical constituents of arial and underground parts of Geum rivale L. (Rosaceae) and the pharmacological activity of its extracts and individual compounds.Materials and methods. The study was carried out using Internet resources (Google Scholar, PubMed) and library databases (e-Library, Scopus, Web of Science). The main research methods were a review and analysis of the literature data on the topic for the period from 1958 up to the present.Results. For the period from 1958 up to the present more than 80 components in the arial and underground parts of G. rivale have been identified.  Among them there were components of the essential oil, phenolic acids and coumarins, aglycones of flavonoids, including luteolin, apigenin, quercetin and kaempferol, as well as a number of their glycosides and glucuronides, ellagitannins (hemin A, B, C, D, pedunculagin, stachiurin/casuarinin, tellimagrandin I). Some aspects of the pharmacological activity of total extracts and individual secondary metabolites of G. rivale have been studied, anti-inflammatory, antioxidant, antimicrobial, antiviral activities have been experimentally confirmed.Conclusion. The analysis of the literature data showed that a further study of the composition of metabolites of G. rivale and their pharmacological activity is an urgent task, the solution of which will expand the range of use of this plant in medical practice and consider G. rivale as a promising source of pharmaceutical substances for the creation of new drugs and biologically active additives.